2019
DOI: 10.3389/fpls.2019.00217
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression of Serine Hydroxymethyltransferase-3 From Rice Confers Tolerance to Salinity Stress in E. coli and Arabidopsis

Abstract: Among abiotic stresses, salt stress adversely affects growth and development in rice. Contrasting salt tolerant (CSR27), and salt sensitive (MI48) rice varieties provided information on an array of genes that may contribute for salt tolerance of rice. Earlier studies on transcriptome and proteome profiling led to the identification of salt stress-induced serine hydroxymethyltransferase-3 (SHMT3) gene. In the present study, the SHMT3 gene was isolated from salt-tolerant (CSR27) rice. OsSHMT3 exhibited salinity-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 101 publications
0
20
0
Order By: Relevance
“…In A. thaliana , a ubiquitin-specific protease UBP16 interacts with AtSHMT1 to stabilize it, and they cooperate to increase Na + /H + antiport activity under salt stress ( Zhou et al, 2012 ). In rice, the overexpression level of OsSHMT3 was found to be up-regulated in a salt-tolerant line ‘CSR27′( Mishra et al, 2016 ; Mishra et al, 2019 ). Overexpression of ApSHMT (a gene isolated from cyanobacterium) in Escherichia coli.…”
Section: Discussionmentioning
confidence: 99%
“…In A. thaliana , a ubiquitin-specific protease UBP16 interacts with AtSHMT1 to stabilize it, and they cooperate to increase Na + /H + antiport activity under salt stress ( Zhou et al, 2012 ). In rice, the overexpression level of OsSHMT3 was found to be up-regulated in a salt-tolerant line ‘CSR27′( Mishra et al, 2016 ; Mishra et al, 2019 ). Overexpression of ApSHMT (a gene isolated from cyanobacterium) in Escherichia coli.…”
Section: Discussionmentioning
confidence: 99%
“…Serine hydroxymethyltransferase is involved in the reversible interconversion of Ser and Gly, participates in amination and decarboxylation reactions, and plays an important role in the cell-carbon metabolic pathway ( Bauwe and Kolukisaoglu, 2003 ; Voll et al, 2006 ). Previous studies mainly focused on the function of SHMT genes under abiotic stresses such as light intensity, salt, and drought ( Voll et al, 2006 ; Cui et al, 2019 ; Mishra et al, 2019 ); however, studies on the role of the SHMT gene family in biotic stresses and its evolutionary relationship in important crops at the genomic level have been limited. Wheat is a heterologous hexaploid composed of three subgenomes A, B, and D. Studies reveal that hybridization of T. urartu (AA) and an Ae.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis , AtSHM1 is involved in the photorespiratory pathway ( McClung et al, 2000 ; Moreno et al, 2005 ; Voll et al, 2006 ). The mutant shm1-1 showed a lethal photorespiratory phenotype caused by photorespiration deficiency when grown at ambient CO 2 ( Voll et al, 2006 ), and showed a more susceptible phenotype than the wild type when infected with biotrophic and necrotrophic pathogens, as well as enhanced susceptibility to salt, drought, and high light stress ( Moreno et al, 2005 ; Liu et al, 2019 ; Mishra et al, 2019 ). AtSHM2 is a functional mitochondrial SHM , and the expression of SHM2 is restricted to the vasculature of leaves ( Engel et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serine hydroxymethyltransferase (SHMT; EC 2.1.2.1) is involved in the photorespiratory pathway of oxygenic photosynthetic organisms [75]. SHMT, a pyridoxal phosphatedependent enzyme, plays a pivotal role in cellular one-carbon pathways by catalyzing the interconversion of L-serine to glycine and tetrahydrofolate to 5,10-methylenetetrahydrofolate for synthesis of nucleic acids, and proteins [76].…”
Section: Plos Onementioning
confidence: 99%